2022
DOI: 10.1186/s12866-022-02623-w
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic-based analysis of 3D macrophage migration after stimulation by Mycobacterium, Salmonella and Escherichia

Abstract: Macrophages play an essential role in the process of recognition and containment of microbial infections. These immune cells are recruited to infectious sites to reach and phagocytose pathogens. Specifically, in this article, bacteria from the genus Mycobacterium, Salmonella and Escherichia, were selected to study the directional macrophage movement towards different bacterial fractions. We recreated a three-dimensional environment in a microfluidic device, using a collagen-based hydrogel that simulates the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Collagen hydrogel density can be modified by altering collagen concentration in the hydrogel, which affects macrophage migration. In a dense collagen gel, macrophages migrate less than in a highly porous collagen gel ( Ford et al, 2019 ; Pérez-Rodríguez et al, 2022 ). Another method of controlling density is by integrating soluble particles into a hydrogel, which, upon dissolution, leaves pores with a specific size ( Lee et al, 2017 ).…”
Section: Immune Cell Extravasation In Organs-on-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen hydrogel density can be modified by altering collagen concentration in the hydrogel, which affects macrophage migration. In a dense collagen gel, macrophages migrate less than in a highly porous collagen gel ( Ford et al, 2019 ; Pérez-Rodríguez et al, 2022 ). Another method of controlling density is by integrating soluble particles into a hydrogel, which, upon dissolution, leaves pores with a specific size ( Lee et al, 2017 ).…”
Section: Immune Cell Extravasation In Organs-on-chipmentioning
confidence: 99%
“…For example, in the first lung on chip published by Huh et al ( Huh et al, 2010 ), neutrophils were migrating towards the site of infection, but migration dynamics could not be quantified, as it was occurring vertically across a porous membrane, and the immune cell migrated out of focus. Thus, to fully image the extravasation process, generating a model where immune cells migrate in a horizontal plane instead of vertically across a membrane is essential, as exemplified by multiple experimental designs ( de Haan et al, 2021 ; Pérez-Rodríguez et al, 2022 ; Riddle et al, 2022 ). Live imaging of one focal plane can be carried out, and immune cell migration can be tracked.…”
Section: Immune Cell Extravasation In Organs-on-chipmentioning
confidence: 99%
“…Sandra et al designed a microfluidic system for the in situ investigation of the macrophage cellular processes in the presence of bacteria. [12] The system consisted of two adjacent chambers interconnected by numerous nanochannels at the wall between the two chambers, which blocked the cells in the individual chambers, but allowed the liquid to diffuse between the chambers. When bacteria are present in the bacterial chamber, the macrophages in the chamber move directly to the chamber where the bacteria are present.…”
Section: Animal Cellsmentioning
confidence: 99%
“…The emergence of microfluidic technology has provided a broad stage for the investigation of cellular processes through real-time in situ monitoring of biomarkers during cell culture. Microfluidic platforms, also known as lab-on-a-chip, [8] provide an ideal tool for the real-time in situ monitoring of biomarkers at the cellular level, [9] and are thus widely used in cell culture, [10] cell differentiation, [11] cell migration, [12] and cell-tocell communication. [13] The first microfluidic platform dates back to 1975, when James et al reported a gas chromatographic air analyzer fabricated on a silicon wafer.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches include but are not limited to certain protocols for MALDI-TOF MS (Drancourt, 2010;Meex et al, 2012;Hoyos-Mallecot et al, 2014;Idelevich et al, 2014;Machen et al, 2014;Verroken et al, 2015;Zhou et al, 2017), infrared spectroscopy (FTIR) (Ojeda and Dittrich, 2012;Zarnowiec et al, 2015;Vogt et al, 2019), nuclear magnetic resonance (NMR) spectroscopy (Romaniuk and Cegelski, 2015;Palama et al, 2016), capillary electrophoresis (incl. capillary isoelectric focusing (Ruzicka et al, 2016;Xu and Sun, 2021), electrical field-flow fractionation (Saenton et al, 2000;Reschiglian et al, 2002), microfluidic devices (Kim et al, 2012;Zhou et al, 2019;Peŕez-Rodrıǵuez et al, 2022) and Raman spectroscopy (Franco-Duarte et al, 2019). Recently, Raman spectroscopy has been undergoing a boom in microbiology, as many studies suggest its potential for the identification of microbes, their virulence factors, detection of metabolic changes, and last but not least, single-cell analyses of microbial cells.…”
Section: New Approachesmentioning
confidence: 99%